2015
DOI: 10.1007/s12035-015-9371-3
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of Influence ERCC Polymorphisms Confer on the Development of Brain Tumors

Abstract: Within DNA repair genes, there lie a number of single nucleotide polymorphisms that may impair protein function and attenuate DNA repair capability, resulting in genomic instability and individual predisposition to malignancies. The purpose of this study was to assess the previously reported inconsistent association of polymorphisms in ERCC1 (rs11615, rs3212986), ERCC2 (rs13181, rs1799793, rs238406), and ERCC5 (rs17655) with the development of brain tumors. In the present work, we carried out a comprehensive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
(57 reference statements)
1
11
0
Order By: Relevance
“…Additionally, lncRNAs were also reported to function in tumor drug resistance through coding transcription modulation (38). In our study, some function of molecules in the drug resistance related MMR and NER signaling pathway were upregulated in U87TR cells, e.g., MSH3 in MMR and ERCC1/2 in NER signaling, which were revealed by the pathway analysis on mRNAs and were consistent with previous reports (39,40). …”
Section: Discussionsupporting
confidence: 92%
“…Additionally, lncRNAs were also reported to function in tumor drug resistance through coding transcription modulation (38). In our study, some function of molecules in the drug resistance related MMR and NER signaling pathway were upregulated in U87TR cells, e.g., MSH3 in MMR and ERCC1/2 in NER signaling, which were revealed by the pathway analysis on mRNAs and were consistent with previous reports (39,40). …”
Section: Discussionsupporting
confidence: 92%
“…The rs3212986 polymorphism, located in the 3′‐untranslated region of ERCC1 and the coding region of CD3EAP, may affect DNA repair capacity by reducing the stability of ERCC1 mRNA . As we expected, a case–control study showed rs3212986 AA genotype was related with an increased risk of glioma . However, for the pancreatic cancer subjects with the CC genotype of rs3212986 compared with those with the AA genotype, no such significance was found .…”
Section: Discussionmentioning
confidence: 73%
“…Because the XPG gene is an indispensable component of the NER pathway, SNPs in XPG may alter the expression or function of XPG thereby modifying the risk of cancer. Most previous meta-analyses of the association between SNPs in XPG and cancer risk have focused on rs17655 G>C [5659]. However, recent studies have shown that other SNPs in XPG may also be associated with cancer risk.…”
Section: Discussionmentioning
confidence: 99%